Integration of Ethnoscience into Environment-STEM Learning in Elementary Schools : An Islamic Education Perspective - Diah Wahyuningsih; Tri Kinasih; Ika Maryani (Al-Ulum, 2025)
This study examines the integration of ethnoscience into Environment-STEM learning in elementary schools in Pacitan Regency from an Islamic education perspective. Using a qualitative case study in ten public and Islamic elementary schools, data were collected through observations, interviews, and documentation and analyzed interactively. The findings show that local wisdom was transformed into Environment-STEM modules through Batik Pace, Wayang Beber, and local traditions, while Project-Based Learning promoted contextual and environmental problem solving. Islamic education served as a pedagogical framework by integrating the values of khalifah fil ardh, amanah, ihsan, and mizan into learning objectives, instructional strategies, and assessment. The study proposes a novel Environment-STEM pedagogical model that advances environmental literacy, scientific literacy, sustainable character, and culturally responsive education.